Cinacalcet Treatment Significantly Improves All-Cause and Cardiovascular Survival in Dialysis Patients: Results from a Meta-Analysis - Yuan Zu; Xiangxue Lu; Jinghong Song; Ling Yu; Han Li; Shixiang Wang (Kidney & Blood Pressure Research, 2019)
Objective: To assess the long-term effects including all-cause mortality, cardiovascular mortality, and fracture incidence, of cinacalcet on secondary hyperparathyroidism (SHPT) in patients on dialysis. Methods: PubMed, Embase, and the Cochrane Central Register of Controlled Trials were searched from their inception to October 2018. Randomized controlled trials (RCTs) and cohort design prospective observational studies assessing cinacalcet for the treatment of SHPT in dialysis patients were included. Data extraction was independently completed by 2 authors who determined the methodological quality of the studies and extracted data in duplicate. Study-specific risk estimates were tested by using a fixed effects model. Results: A total of 14 articles with 38,219 participants were included, of which 10 RCTs with 7,471 participants and 4 prospective observational studies with 30,748 participants fulfilled the eligibility criteria. Compared with no cinacalcet, cinacalcet administration reduced all-cause mortality (relative risk [RR] 0.91, 95% CI 0.89–0.94, p < 0.001) and cardiovascular mortality (RR 0.92, 95% CI 0.89–0.95, p < 0.001), but it did not significantly reduce the incidence of fractures (RR 0.93, 95% CI 0.87–1.00, p = 0.05). Conclusions: The results of this meta-analysis indicated that the treatment of SHPT with cinacalcet may in fact reduce all-cause mortality and cardiovascular mortality among patients receiving maintenance dialysis.